Address Presenting the Ninth Annual Report - Black, Eugene R. (World Bank, Washington, DC, 2019)
Eugene R. Black, President of the International Bank for Reconstruction and Development, greeted two new member countries, Indonesia and Israel. He reviewed Bank lending operations, which continues to grow. He commented on the dangers of supplier credits in situations where long-term finance is more appropriate. He mentioned the technical and financial assistance extended by the Bank to development institutions in many countries, including the construction of electric power capacity.